2014
DOI: 10.1002/dev.21199
|View full text |Cite
|
Sign up to set email alerts
|

Social aversive stimuli presented to the mother produce the precocious expression of fear in rat pups

Abstract: During the stress hypo-responsive period, rat pups do not display fear responses toward adult males, yet they exhibit distress behavior in isolation. Since the mother modulates her offspring's affective development, we hypothesized that by altering the mother's behavior, a prolonged stressful situation would modify the ontogeny of the fear responses and distress behaviors in pups. Therefore, we repeatedly exposed the mother-litter dyad to different socially stressful stimuli and subsequently evaluated in 8-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 73 publications
(129 reference statements)
3
17
0
Order By: Relevance
“…The indication that ancestral stress enhances the vulnerability to hyperactive and anxiety-like behaviours agrees with findings made in prenatally stressed animals45464748. Our results also validate those of other studies that found precocious development of fear-related behaviours in rat pups after maternal stress49 and CORT exposure50. A possible mechanism is that stress-induced hormonal imbalance prior to pubescence may accelerate testicular development, thus increasing the brain’s exposure to androgens during development followed by a decline in testosterone during adulthood51.…”
Section: Discussionsupporting
confidence: 91%
“…The indication that ancestral stress enhances the vulnerability to hyperactive and anxiety-like behaviours agrees with findings made in prenatally stressed animals45464748. Our results also validate those of other studies that found precocious development of fear-related behaviours in rat pups after maternal stress49 and CORT exposure50. A possible mechanism is that stress-induced hormonal imbalance prior to pubescence may accelerate testicular development, thus increasing the brain’s exposure to androgens during development followed by a decline in testosterone during adulthood51.…”
Section: Discussionsupporting
confidence: 91%
“…Rodent work indicates that infant offspring can acquire fear to a conditioned stimulus vicariously through their mother (Chang & Debiec, ; Debiec & Sullivan, ). Furthermore, exposing mothers to a socially aversive stimulus (i.e., adult male intruder) in the presence of their infant offspring leads to the precocious expression of fear to that stimulus in the offspring (Zuluaga, Agrati, Uriarte, & Ferreira, ). Given that offspring of previously stressed mothers exhibit atypical affective development (i.e., precocious fear behavior; Kan et al, ), it is possible that displays of heightened fear in mothers following maternal‐separation may play a role in those findings.…”
Section: Experiments 4: Maternal Anxietymentioning
confidence: 99%
“…For most mammals, especially during the neonatal period, the mother is the main source of stimulation. As such, different amounts or types of maternal care received modify many aspects of the neurobehavioral development (Kaffman and Meaney, 2007;Ladd et al, 2000;Loman and Gunnar, 2010;Zuluaga et al, 2014).…”
Section: Early-life Environmentmentioning
confidence: 99%